Antecedents Of Career Optimism, Career Success, And Competence For Career Sustainability As A Professional Lecturer In Indonesia - Hening Nakuloadi; Nur Wening; Evada Rustina; Teguh Widodo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to examine the relationship between the variables of career optimism, career success, and competence on career sustainability directly and indirectly in private universities in Indonesia. This study uses quantitative methods with structural equation modelling analysis techniques. The result is that career optimism has no effect on career competence, but career optimism has a positive effect on career sustainability. Furthermore, the results of indirect testing found that career competence is not able to intervene in the relationship between career optimism variables and career sustainability, but career success is able to strongly mediate the relationship between career optimism variables and career competence and strongly moderate the relationship between career optimism variables and career sustainability. The implication of this research is that all lecturers are expected to start thinking about their career sustainability, either by improving their abilities or taking higher education to reach a professional level as lecturers and educators.